Profilin choreographs actin and microtubules in cells and cancer - Pimm, Morgan L. (Int Rev Cell Mol Biol, 2020)
Actin and microtubules play essential roles in aberrant cell processes that define and converge in cancer including: signaling, morphology, motility, and division. Actin and microtubules do not directly interact, however shared regulators coordinate these polymers. While many of the individual proteins important for regulating and choreographing actin and microtubule behaviors have been identified, the way these molecules collaborate or fail in normal or disease contexts is not fully understood. Decades of research focus on Profilin as a signaling molecule, lipid-binding protein, and canonical regulator of actin assembly. Recent reports demonstrate that Profilin also regulates microtubule dynamics and polymerization. Thus, Profilin can coordinate both actin and microtubule polymer systems. Here we reconsider the biochemical and cellular roles for Profilin with a focus on the essential cytoskeletal-based cell processes that go awry in cancer. We also explore how the use of model organisms has helped to elucidate mechanisms that underlie the regulatory essence of Profilin in vivo and in the context of disease.